Unnatural history - Kellerman, Jonathan (New York : Ballantine Books, 2023)
When a wealthy photographer, who had recently received rave media attention for his images of homeless people in their personal (3z(Bdream(3y (Bsituations, is shot to death, Dr. Alex Delaware and Detective Milo Sturgis, when new murders arise, are confronted by one of the deadliest threats they$1 (Bve ever faced.s
Keywords: Delaware, Alex -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Photographers -- Fiction; Los Angeles (Calif.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction